2013
DOI: 10.3762/bjnano.4.75
|View full text |Cite
|
Sign up to set email alerts
|

New hybrid materials based on poly(ethyleneoxide)-grafted polysilazane by hydrosilylation and their anti-fouling activities

Abstract: SummaryThe objective of this work was to develop new coating materials based on poly(ethyleneoxide) (PEO), which was grafted onto polysilazane (PSZ) by hydrosilylation. Three types of PEO with different molecular weights (350, 750, 2000 g/mol) were studied. The kinetics and yields of this reaction have been surveyed by 1H and 13C NMR spectroscopy. The PEO grafting-density onto PSZ by hydrosilylation increases with a reduction of the S–H/allyl ratio and a decrease of the PEO chain-length. The PEO-graft-PSZ (PSZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…LIVE/DEAD bacterial cell staining assay ascribed the decrease of living bacteria adhesion to the biocidal effects of silver nanoparticles rather than antifouling effects. Silver nanoparticles have been found to be more potent to kill Gram‐negative bacteria than Gram‐positive ones . Therefore, the antibacterial improvement by biocidal silver nanoparticles to PU‐DA‐F is more significant for Gram‐negative bacteria ( E. coli ) than that for Gram‐positive bacteria ( S. aureus ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LIVE/DEAD bacterial cell staining assay ascribed the decrease of living bacteria adhesion to the biocidal effects of silver nanoparticles rather than antifouling effects. Silver nanoparticles have been found to be more potent to kill Gram‐negative bacteria than Gram‐positive ones . Therefore, the antibacterial improvement by biocidal silver nanoparticles to PU‐DA‐F is more significant for Gram‐negative bacteria ( E. coli ) than that for Gram‐positive bacteria ( S. aureus ).…”
Section: Discussionmentioning
confidence: 99%
“…Silver nanoparticles have been found to be more potent to kill Gram-negative bacteria than Gram-positive ones. 33 Therefore, the antibacterial improvement by biocidal silver nanoparticles to PU-DA-F is more significant for Gram-negative bacteria (E. coli) than that for Gram-positive bacteria (S. aureus). The fluoroalkyl-coated surfaces show excellent antifouling activity due to extremely low surface energy of the 1H, 1H, 2H, 2H-perfluorodecanethiol which result the easy release of the adhered microbes during washing process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, for bioapplications, it is necessary to apply coatings to the polysiloxanes' surfaces by chemical modification of grafting. [135][136][137][138] Nguyen and coworkers proposed the grafting of polysilazane PSZ with poly(ethylene oxide) PEO by hydrosilylation using Karstedt's catalysts [139]. They investigated marine bacteria and found that the grafting density of PEO onto PSZ strongly influenced the bacterial adhesion.…”
Section: Printing and Inksmentioning
confidence: 99%
“…Such biofilm is formed by the adhesion and growth of bacteria and other biomacromolecules on an implant surface . Therefore, it is necessary to develop antifouling polymer surfaces with optimum surface structures for the purpose of preventing unwanted bioadhesion at surfaces …”
Section: Introductionmentioning
confidence: 99%